Assessment of the effect of continuous theta burst stimulation of the motor cortex on manual dexterity in non‐human primates in a direct comparison with invasive intracortical pharmacological inactivation. (13th August 2019) - Roux, Camille; Kaeser, Mélanie; Savidan, Julie; Fregosi, Michela; Rouiller, Eric M.; Schmidlin, Eric
Abstract: Non‐invasive reversible perturbation techniques of brain output such as continuous theta burst stimulation (cTBS), commonly used to modulate cortical excitability in humans, allow investigation of possible roles in functional recovery played by distinct intact cortical areas following stroke. To evaluate the potential of cTBS, the behavioural effects of this non‐invasive transient perturbation of the hand representation of the primary motor cortex (M1) in non‐human primates (two adult macaques) were compared with an invasive focal transient inactivation based on intracortical microinfusion of GABA‐A agonist muscimol. The effects on the contralateral arm produced by cTBS or muscimol were directly compared based on a manual dexterity task performed by the monkeys, the "reach and grasp" drawer task, allowing quantitative assessment of the grip force produced between the thumb and index finger and exerted on the drawer's knob. cTBS only induced modest to moderate behavioural effects, with substantial variability on manual dexterity whereas the intracortical muscimol microinfusion completely impaired manual dexterity, producing a strong and clear cortical inhibition of the M1 hand area. In contrast, cTBS induced mixed inhibitory and facilitatory/excitatory perturbations of M1, though with predominant inhibition. Although cTBS impacted on manual dexterity, its effects appear too limited and variable in order to use it as a reliable proof of cortical vicariation mechanism (cortical area replacing another one) underlying functional recovery following a cortical lesion in the motor control domain, in contrast to potent pharmacological block generated by muscimol infusion, whose application is though limited to an animal model such as non‐human primate. Abstract : Continuous theta burst transcranial magnetic stimulation (cTBS) of the primary motor cortex (M1) in macaques induced a modest to moderate, and variable, effect on manual dexterity performance with the contralateral hand, in sharp contrast to a pharmacological inactivation of M1 (intracortical infusion of muscimol), leading to hand paresis, with total incapacity to grasp and pull a drawer.